معالم تربية الطفل في الإسلام: Child Raising in Islam - Mahyoub Murshed, Amer Abdulwahab; Abdou Amer, Iftikhar Ali (Journal of Islamic Educational Research, 2019)
This research consists of a legitimate view of raising children, which should be taken care of by parents and a society that is reflected in Islamic directives and educational policies so that the child undergoes special education and direct guidance in the implantation of religion and habituate the child to observe God in obeying His commands and avoiding His prohibitions. The importance of parental responsibility relays on this stage, if they succeed in raising their children the family lives a happy life and if they neglected and fail in raising their children they will suffer a lot and the most important landmarks of raising children is faith, emotional, moral, social, mental landmarks. The methodology used in this research is inductive descriptive approach for viewing the best way for raising children. The aim of the research is to focus on the prophetic methods that are beneficial for enlighten the child at this stage. The important result is that the child must be treated in a sophisticated manner to promote the love of Islamic values and morals, and staying away from cruelty and its physical and moral aspects, and to know the needs and the reactions of children.